New insights from network analysis on the biogeography of antiarchs (jawed stem-Gnathostomata) - Pan, Zhao-Hui; Niu, Zhi-Bin; Meng, Fan-Yue; Zhu, Min (Palaeoworld, 2024)
Although many hypotheses have been proposed on the biogeographic evolution of early vertebrates in Silurian and Devonian, it is still difficult to reach a consensus. DeepBone.org is a specimen-based online database hosting data of vertebrate paleontology and paleoanthropology. Here we use comprehensive records of stem gnathostomes in DeepBone to analyse the historical biogragraphy of antiarchs, a primitive group of jawed stem-Gnathostomata. We propose a network analysis-based approach to help quantify and identify pivotal biogeographic provinces. We first segmented biogeographic provinces following the conventional hypothesis and then constructed a directed-weighted temporal-biogeographic network using the Bray-Curtis dissimilarity. Finally, we proposed Evolutionary Importance (EI), a novel algorithm to identify the pivotal province, which has a substantial impact on the constituent members of the provinces in the following age quantitatively. Six biogeographic provinces were evaluated including East Gondwana, Pan-Cathaysia, Central Asia, Baltica, Siberia, and Laurentia. The EI score analysis reveals that the Pan-Cathaysia in Lochkovian is the most crucial province for antiarchs. The Siberia, Baltica, and Central Asia provinces in Givetian and Frasnian are essential to the dispersal of antiarchs, whereas the Central Asia province might act as a ‘stepping-stone’ for the dispersal of euantiarchs. Yunnanolepidoids, which are the most plesiomorphic antiarchs, were endemic in the Pan-Cathaysia, highlighting the origin of Antiarcha in this province. Sinolepidoids also originated in the Pan-Cathaysia and were endemic in the Pan-Cathaysia and East Gondwana provinces. Among euantiarchs, bothriolepidoids originated and differentiated in the Pan-Cathaysia province, while asterolepidoids originated and differentiated in the East Gondwana province.